Alexithymic and somatisation scores in patients with temporomandibular pain disorder correlate with deficits in facial emotion recognition. (9th November 2012) - Haas, J.; Eichhammer, P.; Traue, H. C.; Hoffmann, H.; Behr, M.; Crönlein, T.; Pieh, C.; Busch, V.
Summary: Current studies suggest dysfunctional emotional processing as a key factor in the aetiology of temporomandibular disorder (TMD). Investigating facial emotion recognition (FER) may offer an elegant and reliable way to study emotional processing in patients with TMD. Twenty patients with TMD and the same number of age‐, sex‐ and education‐matched controls were measured with the Facially Expressed Emotion Labelling (FEEL) test, the 26‐item Toronto Alexithymia Scale (TAS‐26), the Screening for Somatoform Symptoms (SOMS‐2a), the German Pain Questionnaire and the 21‐item Hamilton Depression Rating Scale (HAMD). The patients had significantly lower Total FEEL Scores ( P  = 0·021) as compared to the controls, indicating a lower accuracy of FER. Furthermore, we were able to demonstrate significant group differences with respect to the following issues: patients were more alexithymic ( P  = 0·006), stated more somatoform symptoms ( P  < 0·004) and had higher depressive scores in the HAMD ( P  < 0·003). The factors alexithymia and somatisation could explain 31% (adjusted 27%) of the variance of the FEEL Scores in the sample. The estimation of the standardised regression coefficients suggests an equivalent influence of TAS‐26 and SOMS‐2a on the FEEL Scores, whereas 'group' (patients versus healthy controls) and depressive symptoms did not contribute significantly to the model. Our findings highlight FER deficits in patients with TMD, which are partially explained by concomitant alexithymia and somatisation. As suggested previously, impaired FER in patients with TMD may further point to probable aetiological proximities between TMD and somatoform disorders.